Ang kabit ni Mrs. Montero - Gallaga,Peque; Reyes, Lore. (Quezon City Viva Video., 1999)
Cal Montero, a wealthy filmmaker recently paralyzed from the waist down, goes to his hacienda in Negros for recovery and physical therapy. He's morose, but tries to stay in full control. Annie, his therapist, works each of his joints and may have designs on replacing Cal's wife, Gail. Gail is looking for tenderness, and finds it in the shack of Satur, one of the hacienda's workers. Cal and Annie set a spy on Gail, Gail wants to return to Manila to find a job, and unfaithfulness could spark violence. Cal loads his shotgun.
DVD
Edu Manzano, Patricia Javier, Gardo Versoza
Keywords: Feature Films